Inisiasi Pembuatan Pupuk Organik Cair Dalam Meningkatkan Produksi Tanaman Pangan Di Desa Setiris Kecamatan Muaro Sebo Kabupaten Muaro Jambi - Fathoni, Zakky; Elwamendri, Elwamendri; MT Napitupulu, Dompak; Lubis, Arsyad; Oktari Ulma, Riri (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2023)
The rice agribusiness system includes many subsystems, ranging from the input provider subsystem to the marketing subsystem. If observed, agribusiness subsystem problems occur in all rice-producing areas, including in Jambi Province. One of the impacts that arise due to agribusiness subsystem problems is the decline in the level of production and productivity of rice plants. In order to get the right solution to overcome the level of dependence of farmers on production inputs, namely fertilizers, a series of process management steps were carried out consisting of the preparation of proposals, surveys and analysis of information needs, preparation of extension materials, implementation of extension activities on organic liquid fertilizers, monitoring and evaluation, preparation of service reports, and publication of service articles.The outputs of the activity include expanding knowledge about the production of POC JAKABA fertilizer, the benefits of fertilizers, and how POC JAKABA fertilizer can improve soil quality. Farmers enthusiastically stated that this activity had significant benefits for the sustainability of their farms. The constraints faced by farmers in Setiris village include high dependence on fertilizers, frequent shortages of fertilizers before the planting season, expensive fertilizer prices, pest control, less routine irrigation systems. Farmers are still lazy to utilize agricultural waste. The outputs of this training include expanding knowledge about fertilizer production and how POC JAKABA fertilizer can improve soil quality.